In Vitro and In Vivo Investigation of Potential for Complex CYP3A Interaction for PF‐00251802 (Dagrocorat), a Novel Dissociated Agonist of the Glucocorticoid Receptor. Issue 3 (7th November 2017) - Ripp, Sharon L.; Mukherjee, Arnab; Eng, Heather; Stock, Thomas; Fleishaker, Dona; Checchio, Tina; Tammara, Brinda
Abstract: The dissociated agonists of the glucocorticoid receptor are a novel class of agents in clinical development for rheumatoid arthritis. PF‐04171327 (fosdagrocorat) is a phosphate ester prodrug of PF‐00251802 (dagrocorat), a selective high‐affinity partial agonist of the glucocorticoid receptor, which is further metabolized to PF‐04015475. This study evaluated the cytochrome P450 (CYP)–mediated drug–drug interaction (DDI) potential of PF‐00251802 and PF‐04015475 in vitro and used model‐based prediction approaches to estimate clinical impact. PF‐00251802 is a reversible inhibitor of several CYPs, but modeling has suggested no clinically relevant interaction. PF‐00251802 and PF‐04015475 are time‐dependent inhibitors and inducers of CYP3A in vitro; PF‐00251802 is also a time‐dependent inhibitor of CYP2D6. Model‐based prediction suggested the potential for weak inhibition of CYP3A in vivo. A clinical DDI study was conducted with midazolam, a sensitive CYP3A substrate. A phase 1 open‐label, multiple‐dose study evaluated the effect of PF‐04171327 on midazolam pharmacokinetics and safety in 12 healthy volunteers. Administration of midazolam alone or concomitantly with PF‐04171327 resulted in equivalent pharmacokinetic profiles (AUCinf, 21.17 vs 20.28 ng·h/mL, respectively), indicating that PF‐04171327 had no net effect on CYP3A activity in vivo. These findings support the further development of PF‐00251802 and PF‐04171327 as potential treatments for patients with rheumatoid arthritis (NCT00987038).